Model Management Zakat Productive for Mustahik Empowerment (Case Study: Rumah Amal Salman ITB and DPU Daarut Tauhid, Bandung, Indonesia) - Gina Noviana Yuniar; Hani Hanifah; Bagdja Muljarijadi (Asosiasi Fakultas Ekonomi dan Bisnis Indonesia, 2017)
There are various ways to reduce poverty, one through the distribution of zakat funds for economic empowerment of the poor. The distribution of zakat funds require Institute Amil Zakat (LAZ) are professional and focus on the allocation of zakat funds to productive sectors. By based on financial inclusion, LAZ has function as mediator between the one who gave zakat funds (muzzaki) with the one who received zakat funds (mustahik) hopefully can be an institution which increase productivity of mustahikAnalythic-method descriptive and comparation are used to seen the efeciency of funds management model which come from zakat to poor people by microfinance institution by applied local culture approach as basis connection between microfinance and their client. Survey of field did based on purposive smpling to the amount of microfinance which based on akat, infaq, and shodaqoh (LAZ) were ini Bandung city such as LAZ Rumah Amal Salman and DPU Daarut Tauhid. As a basic for assessment the efectivity channelization microfinance service by use result chain methods that can described the achievement of success through input – output – outcome stages.The result of research showed that local culture has big influence against the achievement from these two microfinance. Coaching and mentoring activities provision values of akhlak became local cultural traits in LAZ Rumah Amal Salman ITB, able to creates independent mustahik and has akhlakul karimah. Meanwhile, in DPU Daarut Tauhid adaptation with local culture made trhough facilitation and business choacing to all mustahik has increase their confidence at beginner stemming from poor society groups. In addition, DPU Daarut Tauhid also do review an evaluation to all mustahik to control mustahik hearts leverage the capital that has given, so that the program can realize the aim to produce zakat productive.Keywords: Institute Amil Zakat, Local Culture, Zakat Produktif